Validation of an Automated Solid-Phase Extraction Method for the Analysis of 23 Opioids, Cocaine, and Metabolites in Urine with Ultra-Performance Liquid Chromatography–Tandem Mass Spectrometry. (1st June 2014) - Ramírez Fernández, María del Mar; Van Durme, Filip; Wille, Sarah M.R.; di Fazio, Vincent; Kummer, Natalie; Samyn, Nele
Abstract: The aim of this work was to automate a sample preparation procedure extracting morphine, hydromorphone, oxymorphone, norcodeine, codeine, dihydrocodeine, oxycodone, 6-monoacetyl-morphine, hydrocodone, ethylmorphine, benzoylecgonine, cocaine, cocaethylene, tramadol, meperidine, pentazocine, fentanyl, norfentanyl, buprenorphine, norbuprenorphine, propoxyphene, methadone and 2-ethylidene-1, 5-dimethyl-3, 3-diphenylpyrrolidine from urine samples. Samples were extracted by solid-phase extraction (SPE) with cation exchange cartridges using a TECAN Freedom Evo 100 base robotic system, including a hydrolysis step previous extraction when required. Block modules were carefully selected in order to use the same consumable material as in manual procedures to reduce cost and/or manual sample transfers. Moreover, the present configuration included pressure monitoring pipetting increasing pipetting accuracy and detecting sampling errors. The compounds were then separated in a chromatographic run of 9 min using a BEH Phenyl analytical column on a ultra-performance liquid chromatography–tandem mass spectrometry system. Optimization of the SPE was performed with different wash conditions and elution solvents. Intra- and inter-day relative standard deviations (RSDs) were within ±15% and bias was within ±15% for most of the compounds. Recovery was >69% (RSD < 11%) and matrix effects ranged from 1 to 26% when compensated with the internal standard. The limits of quantification ranged from 3 to 25 ng/mL depending on the compound. No cross-contamination in the automated SPE system was observed. The extracted samples were stable for 72 h in the autosampler (4°C). This method was applied to authentic samples (from forensic and toxicology cases) and to proficiency testing schemes containing cocaine, heroin, buprenorphine and methadone, offering fast and reliable results. Automation resulted in improved precision and accuracy, and a minimum operator intervention, leading to safer sample handling and less time-consuming procedures.